PKM cara mudah menulis puisi - Rukayah Rukayah; Abd. Hafid; Hasbi Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partner of the Community Partnership Program (PKM) is SD Inpres 3/77 Manurunge. The problem statements are: (1) partner is inaccurate in using diction in writing poetry, (2) partner is difficult to formulate goals in writing poetry, (3) ignoring the use of rhyme, (4) content of poetry is not accordance with the title/theme. The external target is children's poetry which has aesthetic value for publication to the mass media. The method used are:observation, questions and answers (Q&A)/interview, discussion, demonstration, exercise, assignment, work visits. The results achieved are: (1) Participants have knowledge about how to choose diction, (2) areable to formulate goals in writing poetry, (3) have an ability to develop contentwhich is in accordance with the title/theme, (4) have knowledge about the importance of rhymes, and(5) can make poetry by paying attention to the use of diction, writing purpose, content, language style, and rhyme.